Repo-Educ: Repository of Educational Robotics Lesson Plans - Pereira, Aylane Santos; Moura, Merciana Gonçalves Pereira; Gonçalves, Luiz Marcos Garcia; Curvelo, Carla Da Costa Fernandes (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Educational robotics is a practice that has been disseminated in Brazil and in the world, allowing the inclusion of technology in the school environment through stimulating pedagogical activities for students, making them practice teamwork, fine motor coordination, and computational thinking, among other benefits. For the educational robotics classes to be executed in the most effective way, the teacher must be trained to use this tool, and from there propose and/or execute classes that use the technology to help in the teaching of curricular subjects in basic education. However, many teachers do not realize what can be possible with robotics in the classroom, and this often causes them not to choose to learn more about this technology. In this work, we developed a web system called Repo-Educ in which a teacher can access information about robotics lessons created by other teachers, generating ideas about how to apply robotics in their classroom. Using this system, it is possible to transform robotics education by combining knowledge. Even teachers who have never had contact with robotics can start using this technology in the classroom by replicating lessons that are proven to work by other teachers. The system is in the final stages of development to be made available to the educational robotics community.